The Sectarian Factor In Iran’s Regional Foreign Policy In The Post-Islamic Revolution Period - Azimov Habibullokhon; Sobirova Mokhichekhra (Frontline Social Sciences and History Journal, 2025)
The 1979 Islamic Revolution fundamentally transformed the conceptual foundations of Iran’s foreign policy. In the post-revolution period, religious and ideological factors, particularly sectarian considerations, began to play a central role in shaping the country’s regional policy. In the context of sectarian politicization in the Middle East, Iran aligned its foreign policy with Shi’a religious and cultural principles, viewing regional Shi’a communities as a key pillar in strengthening its geopolitical influence. This process not only defined the distinctive features of Iran’s foreign policy but also influenced the formation of a new geopolitical balance in regional security.